Microsoft SharePoint 2010 business intelligence unleashed - Mann, Steve, 1950- (Sams, 2011)
SharePoint 2010 is rapidly emerging as the preferred presentation and deployment system for Business Intelligence (BI) solutions that use the Microsoft technology stack. This is a complete guide to both SharePoint 2010 and BI. This book reflects the unsurpassed real-world experience of five expert consultants at RDA, a Microsoft Gold Partner specializing in delivering advanced BI solutions with SharePoint. The authors offer practical, how-to guidance for every key task involved in building, configuring, and deploying BI solutions within a SharePoint environment, delivering crucial information that can't be found in any other book. They bridge the gap between SharePoint 2010 and SQL Server 2008, carefully guiding technical professionals on utilizing BI data stored in SQL Server databases. Both a hands-on tutorial and a thorough reference, SharePoint 2010 BI Unleashed will be an indispensable resource for every BI developer, implementer, manager, or integrator working with Microsoft technologies.